The Influence of Intellectual Capital and Profitability on Company Value (Empirical Study on Telecommunication and Banking Companies Listed on the Indonesia Stock Exchange in 2018-2022) - MAHARANI, Devinda Setya; STEELYANA, Evy (Journal of Tourism Economics and Policy, 2025)
Advances in technology and science make competition between one company and another more competitive. Intellectual Capital (IC) is an intangible asset that can make a company superior if the company is able to utilize Intellectual Capital properly and efficiently. Profitability is used as an illustration of the company's financial condition with analytical tools to see whether the profitability of a company is good or bad. The success of a company is not only seen from the profitability of a company, but also can be seen from the resources in a company. The view that Intellectual Capital can affect company profitability and provide value to the company states that companies that are able to manage knowledge resources well, companies can compete competitively and have competitive advantages that affect profitability (resource based theory).